CSC138 - Structures Programming / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2023)
This course introduces the students to the techniques of programming using an imperative structured language. It covers single and multi-dimensional arrays, records and file processing concepts. Besides covering the basic syntax and semantics, the course emphasizes on problem solving methodology and modular programming techniques.